Versatile Roles of the Chromatin Remodeler CHD7 during Brain Development and Disease - Feng, Weijun; Shao, Chunxuan; Liu, Hai-Kun (Frontiers in Molecular Neuroscience, 2017)
CHD7 (Chromo-Helicase-DNA binding protein 7) protein is an ATP-dependent chromatin remodeller. Heterozygous mutation of the CHD7 gene causes a severe congenital disease known as CHARGE syndrome. Most CHARGE syndrome patients have brain structural anomalies, implicating an important role of CHD7 during brain development. In this review, we summarize studies dissecting developmental functions of CHD7 in the brain and discuss pathogenic mechanisms behind neurodevelopmental defects caused by mutation of CHD7. As we discussed, CHD7 protein exhibits a remarkably specific and dynamic expression pattern in the brain. Studies in human and animal models have revealed that CHD7 is involved in multiple developmental lineages and processes in the brain. Mechanistically, CHD7 is essential for neural differentiation due to its transcriptional regulation in progenitor cells.